The gastronomical arts in Spain : food and etiquette - De Armas, Frederick A., 1945-; Mandrell, James (Toronto Iberic, 2022)
"The Gastronomical Arts in Spain includes essays that span from the medieval to the contemporary world, providing a taste of the many ways in which the art of gastronomy developed in Spain over time. This collection encompasses a series of cultural objects and a number of interests, ranging from medicine to science, from meals to banquets, and from specific recipes to cookbooks. The contributors consider Spanish cuisine as presented in a variety of texts, including literature, medical and dietary prescriptions, historical documents, cookbooks, and periodicals. They draw on literary texts in their socio-historical context in order to explore concerns related to the production and consumption of food for reasons of hunger, sustenance, health, and even gluttony. Structured into three distinct "courses" that focus on the history of foodstuffs, food etiquette, and culinary fashion, The Gastronomical Arts in Spain brings together the many sights and sounds of the Spanish kitchen throughout the centuries."--